Porous metal-organic structure, method for producing the same, adsorbent material, and method for separating carbon dioxide

CN116903867BActive Publication Date: 2026-10-23KK TOSHIBA +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310154738.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-04-18
Filing Date
2023-02-23
Publication Date
2026-10-23
Estimated Expiration
2043-02-23

AI Technical Summary

Technical Problem

[0006]但是,据本发明人们所知,以往提出的MOF的气体吸附量不充分,另外,由于会被水分解而吸附量降低,因此要求提高对水的耐久性

Benefits of technology

[0025]本发明的实施方式的多孔性金属有机结构体具有气体吸附的选择性,与吸附氮相比能够吸附更多的二氧化碳,并且具有优异的耐水性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

Provided is a porous metal-organic structure having selectivity in gas adsorption and excellent water resistance, an adsorbent material formed from the porous metal-organic structure, and a carbon dioxide separation method using the same. The porous metal-organic structure is characterized by comprising a metal oxalate, a cyclic azo dicarbene compound, and a bidentate organic ligand. An adsorbent material formed from the above porous metal-organic structure, and a carbon dioxide separation method using the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to porous metal-organic structures, methods for manufacturing the same, adsorbent materials formed from porous metal-organic structures, and methods for separating carbon dioxide using the porous metal-organic structures. Background Technology

[0002] In recent years, the greenhouse effect caused by rising carbon dioxide (CO2) concentrations, a contributing factor to global warming, has made international countermeasures for environmental protection a top priority worldwide. As industrial activities are a major source of CO2 production, the need to curb its emissions is increasing, and separation and recovery technologies for suppressing the rise in concentrations of acidic gases, including CO2, are known.

[0003] Chemical absorption is the only known acid gas separation technology developed to date, but it generally suffers from problems such as high separation and recovery energy requirements, decomposition of the adsorbent during operation, and reduced separation and recovery efficiency.

[0004] On the other hand, as an alternative to chemisorption, gas storage devices and gas separation devices using solid gas adsorption materials are being developed. Activated carbon and zeolite are known as gas adsorption materials, and methods for adsorbing gases onto porous metal-organic frameworks (MOFs) have also been proposed.

[0005] MOFs are network-like solids formed by linking metal ions with organic spacers. Because they form regularly and correctly defined pores capable of adsorbing gas molecules, they can adsorb large quantities of gas. Furthermore, this type of solid gas adsorbent material is characterized by physical adsorption of CO2; compared to chemical adsorption methods using chemical bonding, it exhibits less interaction with CO2, thus reducing the energy required to release the gas.

[0006] However, to the knowledge of the inventors, the gas adsorption capacity of conventionally proposed MOFs is insufficient, and the adsorption capacity decreases due to water decomposition, thus requiring improved water resistance. Therefore, water-resistant MOFs are also being investigated. Although MOFs formed from zinc oxalate and cycloazo divalent carbon-based compounds, as well as MOFs formed from polycarboxylic acid compounds, at least one metal ion selected from metals belonging to groups 2 to 13 of the periodic table, organic ligands capable of polydentate coordination with the metal ion, and aliphatic monocarboxylic acid compounds have been studied, there is a need to further increase the adsorption capacity.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 9-227571

[0010] Patent Document 2: Japanese Patent No. 6586366

[0011] Patent Document 3: International Publication No. 2013 / 069721

[0012] Non-patent literature

[0013] Non-Patent Literature 1: Susumu Kitagawa, Aggregated Metal Complexes, Kodansha Science, 2001, pp. 214-218 (Susumu Kitagawa, Aggregated Metal Complexes, Kodansha Science, 2001, pp. 214-218) Summary of the Invention

[0014] The problem that the invention aims to solve

[0015] The objective of this invention based on the embodiments is to provide a porous metal-organic structure with high water resistance and high adsorption capacity, a method for manufacturing the same, and a method for separating adsorbent material formed from the porous metal-organic structure and carbon dioxide.

[0016] Methods for solving problems

[0017] In order to solve the above problems, the inventors conducted repeated and intensive research and found that a certain porous metal-organic structure has two characteristics: high water resistance and gas adsorption capacity, thus completing the present invention.

[0018] Therefore, the porous metal-organic structure of the present invention is characterized in that the porous metal-organic structure comprises oxalate, cycloazo divalent carbon-based compound and bidentate coordinated organic ligand.

[0019] Furthermore, the method for manufacturing porous metal-organic structures according to embodiments of the present invention is characterized in that, in the presence of a mixed solvent containing water and alcohol, metal oxalate salts, cycloazo divalent carbon-based compounds, and bidentate organic ligands are subjected to temperature conditions of 100°C to 250°C.

[0020] Furthermore, the adsorbent material of the embodiments of the present invention is characterized in that the adsorbent material is formed from the aforementioned porous metal-organic structure.

[0021] Furthermore, the carbon dioxide separation method according to embodiments of the present invention is characterized in that the separation method includes the following steps (I) and (II).

[0022] Step (I): A step of bringing a carbon dioxide-containing gas into contact with the aforementioned porous metal-organic structure, thereby causing the carbon dioxide in the aforementioned carbon dioxide-containing gas to be adsorbed onto the porous metal-organic structure.

[0023] Step (II): A step in which the carbon dioxide adsorbed by the porous metal-organic structure is removed from the porous metal-organic structure with adsorbed carbon dioxide obtained in the aforementioned step (I).

[0024] Invention Effects

[0025] The porous metal-organic structure of the present invention exhibits selective gas adsorption, adsorbs more carbon dioxide than nitrogen, and has excellent water resistance. Detailed Implementation

[0026] The implementation method will be described in detail below.

[0027] Porous metal-organic structures

[0028] The porous metal-organic structure of the present invention is characterized in that the porous metal-organic structure comprises a metal oxalate salt, a cycloazo divalent carbon-based compound, and a bidentate coordinated organic ligand.

[0029] In this specification, the term "comprising metal oxalate salts, cycloazo divalent carbon-based compounds, and bidentate organic ligands" does not simply mean that the product is composed of only the three listed components (i.e., "metal oxalate salts," "cycloazo divalent carbon-based compounds," and "bidentate organic ligands"), but also includes the product containing the three listed components as well as other components besides these.

[0030] In the porous metal-organic structure of the embodiments of the present invention, the molar ratio of the cycloazodivalent carbon-based compound to the metal oxalate salt is preferably 2 to 6, and particularly preferably 3 to 5. When the molar ratio of the cycloazodivalent carbon-based compound to the metal oxalate salt is less than 2, the problem of not forming fine pores may sometimes occur. In a particularly preferred embodiment, an excess of 2 moles or more of the cycloazodivalent carbon-based compound can be used relative to 1 mole of the metal oxalate salt.

[0031] In the porous metal-organic structure of the embodiments of the present invention, the molar ratio of the aforementioned bidentate-coordinated organic compound to the aforementioned cycloazodivalent carbon-based compound is preferably 0.02 to 0.1, and particularly preferably 0.03 to 0.07. When the molar ratio of the bidentate-coordinated organic compound to the cycloazodivalent carbon-based compound is less than 0.02, the effect of the bidentate ligand is insufficient. Furthermore, when it exceeds 0.1, it may sometimes hinder the reaction of forming fine pores, and therefore is not preferred.

[0032] The average size of the pores present in the porous metal-organic structure is preferably 0.3 nm to 20 nm, and particularly preferably 0.5 nm to 10 nm. Here, the average size of the pores is the size evaluated using the BJH method.

[0033] The porous metal-organic structures of the embodiments of the present invention exhibit selective gas adsorption, capable of adsorbing more carbon dioxide than nitrogen. Furthermore, the porous metal-organic structures of the embodiments of the present invention also possess excellent water resistance; for example, the water resistance, evaluated by a hydrolysis test conducted by exposure to water vapor at 120°C for one week, shows almost no change in the amount of gas adsorbed before and after the test.

[0034] <Metal Oxalate Salts>

[0035] In embodiments of the present invention, divalent metals are targeted as the metals constituting metal oxalate salts. Preferred metals include zinc ions (Zn). 2+ ), cobalt ions (Co) 2+ Nickel ions (Ni) 2+ ), copper ions (Cu) 2+ Among them, zinc ions (Zn) are particularly preferred. 2+ ).

[0036] The porous metal-organic structure of the embodiments of the present invention can preferably be obtained using a raw material containing a metal oxalate salt. As the aforementioned raw material containing a metal oxalate salt, a substance consisting solely of a metal oxalate salt (i.e., a substance with a metal oxalate salt purity of 100%) can be used, but the purity of the metal oxalate salt, on a weight basis, is more preferably 95% to 100%, and particularly preferably 99.5% to 100%. Furthermore, in the case where the raw material contains multiple metal oxalate salts, the purity of the metal oxalate salt of the type present in a relatively larger quantity has been specified above.

[0037] In embodiments of the present invention, it has been confirmed that when the purity of zinc oxalate is 95% to 100% by weight, it is superior in increasing the amount of gas adsorbed by the effect of the bidentate ligand compared to a higher purity (more than 95% to 100%).

[0038] Generally speaking, raw materials with a purity of 95% to 100% are easier to obtain and are also cheaper than high-purity raw materials. Therefore, the porous metal-organic structure of the present invention not only has significant characteristics, but also has economic advantages and industrial implementation benefits.

[0039] <Cycloazo divalent carbon-based compounds>

[0040] Preferred examples of cycloazocarbyl compounds include heterocyclic compounds with five-membered rings having two to four nitrogen atoms.

[0041] Preferred examples of the aforementioned compounds include imidazole, triazole, and tetraazole compounds. In particular, 1,2,4-triazole compounds are also mentioned. Other examples of cyclic azodivalent carbon-based compounds include 1H-1,2,4-triazole salt-1-formamidinium, 3-amino-1,2,4-triazole salt, imidazole salt, 4-fluoroimidazolium salt, 2-methylimidazolium salt, and 1,2,3,4-tetraazole salt. 1,2,4-triazole salts are particularly preferred. The aforementioned cyclic azodivalent carbon-based compounds can be used alone or in combination of two or more.

[0042] <Bidentate organic ligands>

[0043] In embodiments of the present invention, preferred bidentate organic ligands include substances selected from the following compounds.

[0044] 1,4-Dazabicyclo[2.2.2]octane, pyrazine, 2,5-dimethylpyrazine, 3,3'-bipyridine, 4,4'-bipyridine, 2,2'-dimethyl-4,4'-bipyridine, 1,2-bis(4-pyridyl)ethane, 1,2-bis(4-pyridyl)ethylene, 1,2-bis(4-pyridyl)acetylene, 1,3-bis(4-pyridyl)propane, 1,4-bis(4-pyridyl)butane, 1,4-bis(4-pyridyl)butadiyne, 1,4-bis(4-pyridyl)benzene, 3,6-bis(4-pyridyl)-1,2,4,5-tetraazine, 2,2'-bi-1,6-naphthidine, phenazine, diazonium pyrene, 2,6-Di(4-pyridyl)-benzo[1,2-c:4,5-c']dipyrrole-1,3,5,7(2H,6H)-tetraone, 4,4'-bis(4-pyridyl)biphenylene, N,N'-bis(4-pyridyl)-1,4,5,8-naphthalenetetracarboxylic diimide, trans-1,2-bis(4-pyridyl)ethylene, 4,4'-azopyridine, 1,2-bis(4-pyridyl)ethane, 4,4'-dipyridyl sulfide, 1,2-bis(4-pyridyl)propane, 1,2-bis(4-pyridyl)-diol, N-(4-pyridyl)isonicotinamide, piperazine, and 2-methylpiperazine.

[0045] The aforementioned organic ligands capable of bidentate coordination can be used alone, or two or more can be used in combination.

[0046] In embodiments of the present invention, particularly preferred bidentate organic ligands are 1,2-bis(4-pyridyl)ethylene, 1,3-bis(4-pyridyl)propane, 3,3'-bipyridyl and piperazine.

[0047] In addition, tridentate ligands such as 2,4,6-tris(4-pyridyl)-1,3,5-triazine, tetradentate ligands such as tetra(3-pyridyloxymethylene)methane and tetra(4-pyridyloxymethylene)methane may also be used without impairing the effects of the present invention.

[0048] <Methods for manufacturing porous metal-organic structures>

[0049] The method for manufacturing porous metal-organic structures according to embodiments of the present invention is characterized in that, in the presence of a mixed solvent containing water and alcohol, metal oxalate salts, cycloazo divalent carbon-based compounds and bidentate organic ligands are subjected to temperature conditions of 100°C to 250°C.

[0050] The method for manufacturing the porous metal-organic structure according to the embodiments can be understood as a method comprising the following steps: combining a metal oxalate salt compound and a cycloazo divalent carbon-based compound to form a reaction mixture; and reacting the compounds in the reaction mixture at a selected temperature.

[0051] The reaction steps can be carried out in the presence of water, an organic solvent, or a mixture thereof. In a specific embodiment, the reaction solvent is a mixture of water and an organic solvent. In particular, alcohols can be used as the organic solvent.

[0052] The reaction can be carried out in the presence of water and at least one alcohol, preferably a lower alcohol (methanol, ethanol, propanol or butanol, particularly methanol). The volume ratio of alcohol to water is preferably 0.1 to 10, more preferably 0.2 to 10.

[0053] The reaction temperature is 100℃ to 250℃, preferably 150℃ to 200℃. Additionally, it may include the following steps: raising the temperature from a specific temperature to a target temperature; and lowering the temperature from the target temperature to a specific temperature. Heating is preferably carried out in a pressure vessel. The reaction time is preferably 1 hour to 60 hours, particularly preferably 2 hours to 50 hours.

[0054] According to the method for manufacturing porous metal-organic structures according to the embodiments of the present invention described above, powdered porous metal-organic structures with an average particle size of 0.05 μm to 5 μm, particularly 0.1 μm to 3 μm, can be obtained. Here, the average particle size is the value evaluated by SEM.

[0055] The aforementioned powdered porous metal-organic structure can be formulated into spheroids (granules) as needed. The size of the spheroids (granules), measured by average particle size, is preferably 0.1 mm to 5 mm, and particularly preferably 0.5 mm to 3 mm. The size of the spheroids (granules) is a value obtained by evaluation using a stereomicroscope.

[0056] As a method for forming powdered porous metal-organic structures into spherical particles, methods can be listed such as granulating the powder into a liquid (containing a polymer and an organic solvent, and possibly a surfactant) and forming particles with a desired particle size. Methods using polysulfone, for example [L.Li, J.Yao, P.Xiao, J.Shang, Y.Feng, PA Webley, H.Wang, ColloidPolym.Sci.2013, 291, 2711-2717] and methods using polylactic acid, etc., are preferred.

[0057] Activation of metal-organic structures

[0058] The powdered metal-organic structures and spherical (granular) metal-organic structures of the present invention can be activated as needed.

[0059] For example, by imparting 10 to the above-mentioned powdered porous metal-organic structures or spherical (granular) porous metal-organic structures... -1 Activation is achieved by applying a reduced pressure below Pa and a temperature condition of 40°C to 200°C. Here, activation refers to, for example, removing solvents and water that have entered the pores, thereby increasing the surface area of ​​the adsorbed gas.

[0060] The activation of the metal-organic structure according to the embodiments of the present invention can be achieved under reduced pressure, specifically, at 10 - 1 Pa or below 10 -1 Pa, preferably 10 -1 Pa~10 -4 The process involves heating the material to a temperature of 40°C to 200°C, preferably 60°C to 180°C, under Pa conditions.

[0061] The above activation can also be carried out in stages. Preferably, activation can be performed by adopting the following steps: at 10 -1 The process involves a first step of heating at a temperature of 40°C to 60°C for 1 to 4 hours under reduced pressure below Pa; followed by a second step of heating at a temperature of 100°C to 180°C for 5 to 50 hours.

[0062] In addition, before activating the metal-organic structure by heating under reduced pressure, it may be treated or washed with organic solvents such as methanol, ethanol or acetone, as needed, to remove water or impurities adsorbed on the metal-organic structure to be treated.

[0063] The activated spherical (granular) metal-organic structures are preferably granular, spherical, or cylindrical in shape, with an average particle size of 0.1 mm to 5 mm, more preferably 0.5 mm to 3 mm. Furthermore, the average size of the pores is preferably 0.3 nm to 20 nm (evaluated using the BJH method).

[0064] The number, diameter, or morphology of pores in powdered metal-organic structures tend to become more readily adsorbed gases after the above activation treatment.

[0065] <Adsorbent Materials>

[0066] The adsorbent material of the embodiments of the present invention is characterized in that it is formed from the aforementioned porous metal-organic structure. Here, the porous metal-organic structure refers to the aforementioned powdered porous metal-organic structure, spherical (granular) metal-organic structure, the aforementioned activated powdered porous metal-organic structure, and the activated spherical (granular) metal-organic structure, etc.

[0067] Alternatively, when used as an adsorbent, it is filled into an adsorption tank.

[0068] <Methods for separating carbon dioxide>

[0069] The carbon dioxide separation method according to the embodiments of the present invention is characterized by comprising the following steps (I) and (II).

[0070] Step (I): A step in which carbon dioxide-containing gas is brought into contact with the aforementioned porous metal-organic structure, thereby causing carbon dioxide in the aforementioned carbon dioxide-containing gas to be adsorbed onto the aforementioned porous metal-organic structure.

[0071] Step (II): A step in which the carbon dioxide adsorbed by the porous metal-organic structure is removed from the porous metal-organic structure with adsorbed carbon dioxide obtained in the aforementioned step (I).

[0072] Here, the porous metal-organic structure in process (I) refers to the above-mentioned powdered porous metal-organic structure, spherical (granular) metal-organic structure, and the above-mentioned activated powdered porous metal-organic structure, spherical (granular) metal-organic structure, etc.

[0073] As a gas containing carbon dioxide, specifically, a gas containing carbon dioxide as an essential component, and other gaseous components can include mixtures of two or more of nitrogen, oxygen, methane, hydrogen, water vapor, and carbon monoxide, or mixtures of the above gaseous components with other gaseous components not listed above. Examples include coal combustion gas, natural gas, air, shale gas, etc., or gases that are essentially composed only of carbon dioxide are also considered equivalent to gases containing carbon dioxide.

[0074] The carbon dioxide separation method of the embodiments of the present invention can be applied to carbon dioxide-containing gases with a wide range of CO2 partial pressures from 0.001 atm to 200 atm. Furthermore, the carbon dioxide separation method of the embodiments of the present invention is preferably carried out at a temperature of 0°C to 200°C.

[0075] The carbon dioxide separation method of the embodiments of the present invention can be implemented by pressure swing adsorption or temperature swing adsorption.

[0076] Here, "pressure swing adsorption" refers to an adsorption separation method in which carbon dioxide gas is adsorbed onto an adsorbent under pressure or atmospheric pressure, unadsorbed components are removed, and then the pressure is reduced to allow the adsorbed gas to detach. Conversely, "temperature swing adsorption" refers to an adsorption separation method in which carbon dioxide gas is adsorbed onto an adsorbent at room temperature or low temperature, unadsorbed components are removed, and then the temperature is increased to allow the adsorbed gas to detach.

[0077] When pressure swing adsorption (PSA) is used for carbon dioxide separation, step (II) includes the step of changing the pressure of the porous metal-organic structure (and its periphery) to a level that allows carbon dioxide to escape from the porous metal-organic structure. The escape pressure is preferably 0.005 MPa to 2 MPa, more preferably 0.01 MPa to 0.1 MPa.

[0078] On the other hand, when the carbon dioxide separation method employs temperature-switching adsorption, step (II) includes the step of heating the porous metal-organic structure that has adsorbed carbon dioxide to a temperature at which carbon dioxide can be released from the porous metal-organic structure. The release temperature is preferably 303K to 473K, more preferably 313K to 373K.

[0079] The carbon dioxide separation method according to embodiments of the present invention includes a defined step (I) and a step (II), and each step (I) and step (II) is performed at least once. Step (I) may be performed multiple times, and step (II) may also be performed multiple times. In addition, a step (one cycle) formed by a combination of one step (I) and one step (II) may be repeatedly performed multiple times.

[0080] In the carbon dioxide separation method of the present invention, as a preferred embodiment, there is, for example, a method comprising performing steps (I) and (II) as described below.

[0081] (1) Process (I) → Process (II)

[0082] (2) Process (I) → Process (II)

[0083] (3) Process (I) → Process (I) → Process (I) → Process (II)

[0084] (4) Process (I) → Process (II) → Process (I) → Process (II)

[0085] (5) Process (I) → Process (I) → Process (II) → Process (I) → Process (II)

[0086] The foregoing has described several embodiments of the present invention, but these embodiments are merely illustrative and do not limit the scope of the invention. These embodiments can be implemented in various other ways, and various omissions, substitutions, modifications, or additions can be made without departing from the spirit of the invention. These embodiments and their variations are included in the scope and spirit of the invention, and are included within the scope of the invention as described in the claims and its equivalents.

[0087] Example

[0088] The present invention will now be described in more detail with reference to embodiments and comparative examples, but the present invention is not limited to these embodiments.

[0089] <Example 1>

[0090] Zinc oxalate (261 mg, 1.38 mmol), 1,2,4-triazole (361 mg, 5.2 mmol), and 1,2-bis(4-pyridyl)ethylene (50 mg, 0.27 mmol) were added to a 23 mL autoclave pressure vessel (made by Teflon, a registered trademark), followed by the addition of water (4 mL) and methanol (6 mL).

[0091] A pressure-resistant container containing the above mixture was placed in an oven and heated to 180°C for 2 hours. The temperature was then maintained at 180°C for approximately 48 hours, followed by a 12-hour cooling to room temperature. The contents of the pressure-resistant container were purified to obtain a powdered porous metal-organic structure (MOF). 100% CO2 gas was adsorbed onto the MOF at 20°C, and the adsorption amount was determined based on the weight difference before and after adsorption. The results are shown in Table 1.

[0092] <Example 2>

[0093] Except that 1,3-bis(4-pyridyl)propane was used instead of 1,2-bis(4-pyridyl)ethylene, a powdered porous metal-organic structure (MOF) was obtained in the same manner as in Example 1. 100% CO2 gas was adsorbed onto the MOF at 20°C, and the adsorption amount was determined based on the weight difference before and after adsorption. The results are shown in Table 1.

[0094] <Example 3>

[0095] Except that 3,3'-bipyridine was used instead of 1,2-bis(4-pyridyl)ethylene, a powdered porous metal-organic structure (MOF) was obtained in the same manner as in Example 1. 100% CO2 gas was adsorbed onto the MOF at 20°C, and the adsorption amount was determined based on the weight difference before and after adsorption. The results are shown in Table 1.

[0096] <Example 4>

[0097] Except that piperazine was used instead of 1,2-bis(4-pyridyl)ethylene, a powdered porous metal-organic structure (MOF) was obtained in the same manner as in Example 1. 100% CO2 gas was adsorbed onto the MOF at 20°C, and the adsorption amount was determined based on the weight difference before and after adsorption. The results are shown in Table 1.

[0098] <Comparative Example 1>

[0099] Except for the absence of 1,2-bis(4-pyridyl)ethylene, a powdered porous metal-organic structure (MOF) was obtained in the same manner as in Example 1. 100% CO2 gas was adsorbed onto the MOF at 20°C, and the adsorption amount was determined based on the weight difference before and after adsorption. The results are shown in Table 1.

[0100] Table 1

[0101] Example 1 1.05 Example 2 1.14 Example 3 1.09 Example 4 1.16 Comparative Example 1 1.00

[0102] It was confirmed that Examples 1-4 recovered more CO2 compared to Comparative Example 1.

Claims

1. A porous metal-organic structure, characterized in that, The porous metal-organic structure comprises oxalate, cyclic azo divalent carbon-based compound, and bidentate coordinated organic ligand. The bidentate organic ligand is selected from the group consisting of 1,2-bis(4-pyridyl)ethylene, 1,3-bis(4-pyridyl)propane, 3,3'-bipyridine, and piperazine. The cyclic azo divalent carbon-based compound is 1,2,4-triazole.

2. The porous metal-organic structure according to claim 1, wherein, The molar ratio of the bidentate organic ligand to the cyclic azo divalent carbon-based compound is 0.02 to 0.

1.

3. A method for manufacturing a porous metal-organic structure, characterized in that, In the presence of a mixed solvent containing water and alcohol, oxalates, cyclic azo divalent carbon-based compounds, and bidentate organic ligands were subjected to temperature conditions ranging from 100°C to 250°C. The bidentate organic ligand is selected from the group consisting of 1,2-bis(4-pyridyl)ethylene, 1,3-bis(4-pyridyl)propane, 3,3'-bipyridine, and piperazine. The cyclic azo divalent carbon-based compound is 1,2,4-triazole.

4. An adsorbent material, characterized in that, The adsorbent material is formed from the porous metal-organic structure described in claim 1 or 2.

5. A method for separating carbon dioxide, characterized in that, The separation method includes the following steps (I) and (II). Step (I): A step of contacting a carbon dioxide-containing gas with the porous metal-organic structure according to claim 1 or 2, thereby causing the carbon dioxide in the carbon dioxide-containing gas to be adsorbed onto the porous metal-organic structure. Step (II): A step in which the carbon dioxide adsorbed by the porous metal-organic structure is removed from the porous metal-organic structure with adsorbed carbon dioxide obtained in step (I).

Citation Information

Patent Citations

  • Gas-storing metal complex, its production, gas-storing apparatus and automobile furnished with gas-storing apparatus

    JP1997227571A

  • Metal complex, and adsorbent, absorbent and separator formed of same

    WO2013069721A1

  • Flexible porous material for pressure swing adsorption of CO2 as well as preparation method and application of flexible porous material

    CN118698503A

  • Synthesis of Zinc MOF Materials

    US20210179638A1